Targeting porphyromonas gingivalis to treat Alzheimer's disease and comorbid cardiovascular disease: Developing topics. (7th December 2020) - Ermini, Florian; Rojas, Paola; Dean, Afsah; Stephens, Danielle; Patel, Michele; Haditsch, Ursula; Roth, Theresa; Rodriguez, Leo; Broce, Sean; Raha, Debasish; Nguyen, Mai; Kapur, Shirin; et al.
Abstract: Background: We recently demonstrated the presence of the bacterial pathogen, Porphyromonas gingivalis ( Pg ), and its protease virulence factors, known as gingipains, in greater than 90% of AD brains. Brain gingipain levels significantly correlated with AD diagnosis and tau and ubiquitin pathology. Mechanistic studies in wild type mice demonstrated that Pg invades the brain after infection of the oral cavity, resulting in the development of neuropathology consistent with that of AD. These effects were blocked in mice after oral administration of the gingipain inhibitor COR388. In addition to neuropathology, AD is often accompanied by the comorbidity of cardiovascular disease. Pg has been linked to the development of atherosclerosis and the bacteria are found abundant within atheromatous plaque. We investigated if COR388 was efficacious in treating Pg‐ accelerated atherosclerosis in a rabbit model. Method: Eighteen New Zealand White rabbits on a 13‐week regimen of 0.5% cholesterol diet to induce atherosclerosis were randomized in the study. Twelve rabbits were orally infected with Pg 3x/week for 6 weeks for oral disease induction and 6 rabbits were sham‐infected. Six Pg – infected rabbits were orally administered COR388 10mg/kg once daily for the entire 13 weeks of the study (prevention protocol), and 6 Pg‐ infected rabbits received vehicle for 13 weeks. Six sham‐infected rabbits received vehicle for 13 weeks. At 13 weeks, atherosclerotic plaques were quantified by assessing Sudan IV staining, histology, and ex vivo MRI. Serum levels of C‐reactive protein (CRP) were evaluated as a measure of systemic inflammation. Result: Pg‐infected rabbits exhibited accelerated atherosclerotic disease severity than sham‐infected animals. COR388 diminished this atherogenesis compared to vehicle controls as evidenced by significantly less arterial plaque and a lower intima/media ratio. COR388 treatment also significantly reduced systemic levels of CRP. Conclusion: COR388, a novel lysine‐gingipain inhibitor, is currently being tested in a Phase 2/3 clinical trial to target Pg for the treatment of AD. Based on the current preclinical data reported here, COR388 has the potential to attenuate atheroma formation and systemic inflammation in Pg‐ induced atherosclerosis and therefore may have beneficial effects on comorbid cardiovascular disease in Pg‐ associated AD.